2008
DOI: 10.1097/prs.0b013e318188247b
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Cosmetic Surgery Training in Plastic Surgery Programs in the United States

Abstract: The information collected revealed significant differences in opinions between program directors and senior residents. Senior residents felt deficient in facial cosmetic, minimally invasive, and recently developed body contouring techniques. On the basis of these results and the authors' experience in resident education, changes in cosmetic surgery training are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 10 publications
3
64
1
2
Order By: Relevance
“…These common but negative perceptions naturally contribute to a surgeon's discomfort and reluctance in dealing with these patients. [6][7][8] A recent study by Constantian challenged the stereotype of the secondary rhinoplasty patient. He looked at the motivations, outcomes, and prevalence of unfavorable results in 150 secondary rhinoplasty patients and found that most secondary rhinoplasty patients have a legitimate source of displeasure, and satisfaction was often achieved once the deformity was corrected.…”
Section: Discussionmentioning
confidence: 97%
“…These common but negative perceptions naturally contribute to a surgeon's discomfort and reluctance in dealing with these patients. [6][7][8] A recent study by Constantian challenged the stereotype of the secondary rhinoplasty patient. He looked at the motivations, outcomes, and prevalence of unfavorable results in 150 secondary rhinoplasty patients and found that most secondary rhinoplasty patients have a legitimate source of displeasure, and satisfaction was often achieved once the deformity was corrected.…”
Section: Discussionmentioning
confidence: 97%
“…However, they reported that only small increases in exposure to many minimally-invasive cosmetic procedures could instill significant confidence, enabling them to incorporate such procedures into a practice. 2,4 Despite a move toward making significant improvements in the quality and comprehensiveness of cosmetic surgery training in the United States, the approach to cosmetic surgery training in Canada has changed little over the past 30 years. Resident knowledge is still acquired in the majority of programs through observation of staff and review of journals and textbooks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Morrison et al and Oni et al shed light on the status of aesthetic surgery training among plastic surgery residents in the United States [5, 8]. However, no prior study has performed a head-to-head comparison of the training experience within the three existing plastic surgery training models.…”
Section: Introductionmentioning
confidence: 99%